Low endothelial shear stress, microcalcification activity and high-risk plaque features: merging computational flow modelling, OCT and 18F-NaF PET/CT. (14th October 2021) - Doyle, B J; Kelsey, L J; Majeed, K; Bellinge, J; Parker, L P; Richards, S; Schultz, C J
Abstract: Background: Endothelial shear stress (ESS) has a critical role in endothelial function. Abnormal shear stress leads to endothelial dysfunction, which contributes to arterial plaque initiation and development. Four dimensional magnetic resonance can determine shear stress in the larger arteries but cannot resolve the detail needed to calculate shear stress in the coronary arteries and thus methods such as computational fluid dynamics (CFD) are required. Additionally, a key feature of biologically active plaques is microcalcification activity, and this can be detected using 18F-sodium fluoride (18F-NaF) positron emission tomography (PET). Furthermore, using high resolution optical coherence tomography (OCT), the high-risk features plaques can be visualized and quantified. We aimed to merge these three techniques to investigate if low ESS is associated with high-risk plaque features and active microcalcifications in acute coronary syndrome. Methods: We began by merging OCT images with CTCA images to obtain detailed 3D reconstructions of the target vessel. We then simulated blood flow and calculated the ESS, from which we extracted the area of low ESS (<0.4 Pa). We quantified plaque features using OCT and measured the maximum 18F-NaF uptake, and compared data at both the coronary segment and whole artery level (Figure 1). Results: We investigated 20 arteries from 18 patients which we obtained 38 coronary segments according to the SCCT guidelines. We found that areas of low ESS were were significantly and positively associated with high-risk plaque features: macrophage infiltration (segment, rs=0.33, p=0.043; artery, rs=0.46, p=0.041) and presence of cholesterol crystals (segment, rs=0.45, p=0.005; artery, rs=0.58, p=0.007). Vessel segments with thin-capped fibroatheroma had greater area of low ESS (20 vs 4%). The uptake of 18F-NaF was positively associated with the area of low ESS (segment, rs=0.52, p=0.001; artery, rs=0.64, p=0.002). We found that there were typically more plaque features found in regions of low ESS (Table 1). Conclusion: Here we provide the first data associating low ESS with both high-risk plaque features and active microcalcifications in patients with acute coronary syndrome. Although our sample size is small, these data are encouraging and could lead to better understanding of how best to deem a plaque "high risk". Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Royal Perth Hospital Medical Research Foundation